Blockade of PLD2 Ameliorates Intestinal Mucosal Inflammation of Inflammatory Bowel Disease - Guangxi Zhou; Lin Yu; Wenjing Yang; Wei Wu; Leilei Fang; Zhanju Liu (Hindawi Limited, 2016)
Background. Inflammatory bowel diseases (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), are chronically remittent and progressive inflammatory disorders. Phospholipase D2 (PLD2) is reported to be involved in the pathogenesis of several inflammatory diseases. However, the exact role of PLD2 in IBD is obscure. Methods. PLD2 expression was determined in peripheral blood cells and inflamed mucosa from patients with IBD by qRT-PCR. Colonic biopsies were also obtained from CD patients before and after infliximab (IFX) treatment to examine PLD2 expression. PLD2 selective inhibitor (CAY10594) was administrated daily by oral gavage in DSS-induced colitis mice. Bone marrow neutrophils from colitis mice were harvested to examine the migration using Transwell plate. Results. PLD2 was found to be significantly increased in peripheral blood cells and inflamed mucosa in patients with active IBD. Treatment with IFX could significantly decrease PLD2 expression in intestinal mucosa in patients with CD. Moreover, blockade of PLD2 with CAY10594 could markedly ameliorate DSS-induced colitis in mice and promote neutrophil migration. Conclusions. PLD2 plays a critical role in the pathogenesis of IBD. Blockade of PLD2 may serve as a new therapeutic approach for treatment of IBD.